AN ANALYSIS OF THE SCHOOL PRINCIPAL'S ROLE IN DEVELOPING EDUCATIONAL QUALITY MANAGEMENT AT SMK PLUS DARUL QUR'AN WAL HADIST TELAGA LEBUR SEKOTONG, WEST LOMBOK REGENCY - Sudiati Sudiati; Adi Suroso; Rusno Rusno (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine the role of the school principal in developing educational quality management at SMK Plus Darul Qur'an Wal Hadist Telaga Lebur, as well as to identify the supporting and hindering factors the principal faces in that process. The study employed a qualitative approach, with primary data gathered through in-depth interviews. The informants included the school principal, the vice principal for curriculum affairs, the vice principal for facilities and infrastructure, the head of administrative staff, and several teachers. Data were collected through observation, interviews, and documentation. The findings reveal that the principal's efforts to improve educational quality encompassed improvements across input, process, and output dimensions, with a continuous drive to maximize all available resources. Specific quality improvement measures included: enhancing the professionalism of teaching and non-teaching staff; improving the quality of learning services for students; managing school funding; reforming curriculum resources; upgrading school facilities and infrastructure; and embedding a culture of quality. The supporting factors identified were: well-equipped educational facilities, a young and promising teaching and administrative workforce, and a harmonious relationship between the school and the surrounding community. The hindering factors included: the school's less-than-ideal location near a hilly area, limited use of the internet within the school environment which was restricted mainly to extracurricular activities and select learning tasks, and a number of parents who had yet to fully grasp the school's vision and mission.